2011
DOI: 10.1590/s1413-86702011000300001
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus aureus regulates secretion of interleukin-6 and monocyte chemoattractant protein-1 through activation of nuclear factor kappaB signaling pathway in human osteoblasts

Abstract: Objective: Activation of nuclear factor kappaB by diverse bacteria regulates the secretion of chemokines and cytokines. Staphylococcus aureus (S. aureus)-infected osteoblasts can significantly increase the secretion of interleukin-6 and monocyte chemoattractant protein-1. The aim of this study was to investigate whether S. aureus can activate nuclear factor kappaB in human osteoblasts, and whether the activation of nuclear factor kappaB by S. aureus regulates the secretion of interleukin-6 and monocyte chemoat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 34 publications
2
7
1
Order By: Relevance
“…NF‐κB activation in response to SA infection has previously been demonstrated using immortalized bovine umbilical vein endothelial cells, an event that had direct influence on the process of SA internalization into the host cells, and which could be modulated by known activators of NF‐κB such as TNF‐α and IL‐1β (Oviedo‐Boyso et al, ). A recent study by Ning et al, () has also demonstrated how SA infection of human osteoblasts can activate NF‐κB leading to elevated production and release of IL‐6 and MCP‐1 (Ning et al, ), observations consistent with our SA:HBMvEC infection model.…”
Section: Discussionsupporting
confidence: 89%
“…NF‐κB activation in response to SA infection has previously been demonstrated using immortalized bovine umbilical vein endothelial cells, an event that had direct influence on the process of SA internalization into the host cells, and which could be modulated by known activators of NF‐κB such as TNF‐α and IL‐1β (Oviedo‐Boyso et al, ). A recent study by Ning et al, () has also demonstrated how SA infection of human osteoblasts can activate NF‐κB leading to elevated production and release of IL‐6 and MCP‐1 (Ning et al, ), observations consistent with our SA:HBMvEC infection model.…”
Section: Discussionsupporting
confidence: 89%
“…Other authors have also reported that IL‐6 is released by infiltrating immune cells and it has been demonstrated that the osteoblast is a significant source of this cytokine . The activation of nuclear factor kappaβ (NF‐κβ) in human osteoblasts by Staphylococcus aureus may subsequently regulate the secretion of IL‐6 . However, only one third of the osteoblasts of the present study were positive for IL‐6, whereas the main source in acute cases was bone marrow neutrophils and macrophages.…”
Section: Cells Immunostaining In 30 Samplescontrasting
confidence: 48%
“…The osteoblasts, derived from mesenchymal bone marrow precursors, control the bone remodeling process by synthesizing the components of bone matrix, and by modulating the activity of the bone-resorbing osteoclasts. These cells have also been shown to produce different soluble inflammatory mediators [IL-6, IL-1, TNF-α, receptor activator of NF-κB ligand (RANKL)], following S. aureus infection (Marriott 2004;Somayaji et al 2008;Wright and Nair 2010;Ning et al 2011;Claro et al 2013). Thus, the bone destruction induced by S. aureus exposure results mainly from the inflammatory reaction elicited by the infection, even if some S. aureus lineages that overexpress the newly studied family of PSM peptides share cytolytic properties following invasion of osteoblasts (Rasigade et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Based on research in this field, bacterial adherence and biofilm formation on the implant surface represent major factors involved in the pathogenesis process, providing protection against antimicrobial therapy and host immune responses (Montanaro et al 2011;Ribeiro, Monteiro and Ferraz 2012;Molina-Manso et al 2013). Regarding bone infection, Staphylococcus aureus has been shown to invade osteoblasts, persist intracellularly and induce the secretion of key proinflammatory mediators and potent stimulators of osteoclastogenesis and bone resorption (Alexander et al 2003;Marriott 2004;Marriot et al 2005;Somayaji et al 2008;Wright and Nair 2010;Ning et al 2011;Hamza et al 2013). Several virulence determinants, such as specific microbial surface components recognizing adhesive matrix molecules with in particular the fibronectin-binding proteins (FnBPs), the surface-bound protein A (SpA) or a class of pore-forming toxins named the phenol-soluble modulins (PSMs), have been demonstrated to play a role in S. aureus invasiveness and bone destruction (Wright and Nair 2010;Cassat et al 2013;Claro et al 2013;Rasigade et al 2013).…”
Section: Introductionmentioning
confidence: 99%